Agro-Industrial Residues from Sugar Cane for Energy Use and Application in Energy Storage Devices - Arthur Pimentel; Leonardo Paim (Proceedings)
Obtaining new materials from waste plays an important role in contributing to sustainability and innovation and reducing the environmental impact of industrial activities, thus contributing to the circular economy of the main production process that gives rise to that waste [...]